Influência de soluções com potencial de pigmentação na cor dos dentes após clareamento com peróxido de carbamida a 22% - Correia, Ayla Macyelle de Oliveira [UNESP]; Melo, Bruno Everthon Duarte; Cedraz, Juliana da Silva Barros; da Rocha, Daniel Maranha; dos Santos, Natanael Barbosa; Fragoso, Larissa Silveira de Mendonça (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2017)
The color stability achieved by dental bleaching can be affected by exposure to staining agents present in foods. However, there is scarce research regarding tooth staining during dental bleaching. This study investigated the effect of pigments on the color stability of dental elements during dental bleaching. Blocks obtained from bovine incisors were divided into seven groups (n = 10) in accordance with the staining pigments (distilled water – control; coffee, cola, tea, red wine, chocolate milk and soya sauce (Shoyu). The color was evaluated with a spectrophotometer (Minolta CR-321, Japan) before and after dental bleaching (1st and 14th days), employing the (CIE) L*a*b* system. The dental bleaching procedure was performed using 22% carbamide peroxide gel applied to the sample surface for a period of 1 hour each day, for 14 days. After dental bleaching, the teeth were exposed to 20 ml of staining solution for 5 minutes, at 37ºC and 100 rpm for different periods. During the experiment, the samples were stored in distilled water. Data was analyzed using ANOVA followed by Tukey tests, with a significance level of 5%. Significant differences for ΔE* values (p<0.05) were observed between the groups. The Shoyu group presented a decrease in luminosity (negative value of ΔL*). It could be concluded that all solutions contained pigments that promoted staining on the surface. However, bleached enamel was susceptible to staining with soya sauce (Shoyu), while other substances did not interfere with the dental bleaching.
Influence of solutions with pigmentation potential on tooth color after bleaching using 22% carbamide peroxide
Keywords: Color; Dental materials; Pigmentation; Spectrophotometry; Tooth bleaching